Effect of Corporate Governance Index on Dividend Policy: An Investigation of Textile Industry of Pakistan - Tahir, Safdar Husain; Sohail, Sara; Babar, Saba; Oayyum, Irtaza (Oeconomica Jadertina, 2017)
This study empirically observes the impact of corporate governance index on dividend payout policy by using the data on thirty textile firms listed at Karachi Stock Exchange. The data cover the five-year period from 2009 to 2013. The data were gathered from financial statements of all the sample firms. Multiple regression models were used to check the impact of corporate governance on dividend policy. No effect of corporate governance index on firm dividend policy was found, and the largest shareholders also had no impact on dividend payout policy. A significant positive relationship was found between payout policy and stock value. Gross profit margin and operating profit margin had significant positive impact on the firm’s dividend payout policy. There is a significant correlation between the firm’s performance and payout policy.
Keywords: Corporate Governance Index; Dividend Policy; Textile Industry; Largest Shareholders; Multiple Regression Model